Penentuan Status Mutu Air Tanah Dangkal di Sekitar Tempat Pembuangan Akhir Sampah (TPA) Air Sebakul Kota Bengkulu menggunakan Metode STORET: A Cross-Sectional Study - Deni Agus Triawan; Doni Notriawan; Gustria Ernis (Universitas Airlangga, 2020)
Ground Water quality has a special significance for drinking, hygiene sanitation and domestic water supply. The study aims to understand the distribution of ground water quality in solid waste landfill of Bengkulu City. The following objectives of the study are to determine ground water quality parameters such as pH, total dissolved solid, electrical conductivity, hardness, iron, manganese, nitrate and nitrite. Sampling was carried out at a radius of 0 - 250 meters from the location of the landfill. The results of the pH at 10 sampling points show the values that are quite varied between 6,45 – 7,59; conductivity between 56 µS – 492 µS; TDS between 28 mg/L – 246 mg/L; salinity 32 mg/L – 284 mg/L; Iron (Fe) 0,040 mg/L – 0,323 mg/L; Manganese (Mn) 0,089 mg/L – 0,295 mg/L; Nitrate (NO3-) 0,2 mg/L – 0,8 mg/L and Nitrite (NO2-) 0,006 mg/L – 0,033 mg/L. Based on an assessment with the STORET system, water quality in the study area is classified as good (score =-4) by parameters such as temperature, pH, total dissolved solid, electrical conductivity, hardness, iron, manganese, nitrate and nitrite. By the total sampling sites, all sample site had good-quality water for hygiene sanitation based on STORET method.